2021
DOI: 10.1016/j.radonc.2021.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Intrafraction motion during partial breast irradiation depends on treatment time

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
(55 reference statements)
2
17
3
Order By: Relevance
“…Ricotti et al [9] also do not observe a correlation between the fraction number and patient drift. Fraction duration however does correlate to baseline drift at the end of the fraction where a longer fraction results in a higher drift, as is observed by Reitz et al [7], Hoekstra et al [10] and Wiant et al [11] for breast cancer patients.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Ricotti et al [9] also do not observe a correlation between the fraction number and patient drift. Fraction duration however does correlate to baseline drift at the end of the fraction where a longer fraction results in a higher drift, as is observed by Reitz et al [7], Hoekstra et al [10] and Wiant et al [11] for breast cancer patients.…”
Section: Discussionmentioning
confidence: 67%
“…Wiant et al [11] reports stabilization of the patient only after 6-10 min while monitoring free breathing breast cancer patients using surface guidance. In contrast, Hoekstra et al [10] noted no stabilization for Accelerated Partial Breast Irradiation (APBI) treatments where the mean fraction duration was 26 min. On C-arm linacs volumetric image acquisition requires the extension of the kV-source and imager and rotation of the gantry to the correct starting angle.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To calculate the single-fraction margins for these two techniques, technique-specific systematic and random errors, expressed as 1 standard deviation of a Gaussian distribution, were taken from literature. For VMAT-APBI, these are beam isocenter accuracy, couch accuracy, and intrafraction motion (Table 1) [25][26][27][28][29]. For CyberKnife-APBI, this is the CyberKnife total system error, which combines imaging and beam adjustment errors.…”
Section: Comprehensive Ctv To Ptv Margin Calculationmentioning
confidence: 99%
“…They showed that the PTV margin depends on the treatment time. 66 However, poor image quality because of dominant Compton scattering in MV beams remains a major problem in portal imaging. Furthermore, according to the AAPM Task Group 75 report, a significant disadvantage of kV imaging-based motion monitoring is the extra dose to the patient, particularly at the skin surface.…”
Section: Motion Monitoring Techniques In Breast Cancer Rtmentioning
confidence: 99%